A 43.0% efficient GaInP photonic power converter with a distributed Bragg reflector under high-power 638 nm laser irradiation of 17 W cm−2. (15th April 2021) - Komuro, Yuki; Honda, Shinya; Kurooka, Kazuki; Warigaya, Ryota; Tanaka, Fumiaki; Uchida, Shiro
Abstract: Optical wireless power transmission systems incorporating photovoltaic cells and lasers are expected to serve as next-generation energy supply devices for automobiles and autonomous underwater vehicles. High photoelectric conversion efficiencies over 40% of photovoltaic converters under high-power irradiation over 10 W cm −2 are required for the practical application in these applications. We achieved a high conversion efficiency of 43.0% of GaInP photonic power converter under high-power 638 nm laser irradiation of 17.0 W cm −2 by incorporating multi-crossed finger electrodes and a distributed Bragg reflector. The highest efficiency, 46.0% of GaInP converter cell, was also obtained at 1.1 W cm −2 laser irradiation.